Organic Fertilizer Improve the Growth, Physiological Characters and Yield of Pak Choy - Endang Dwi Purbajanti; Susi Setyawati (Agrosains : Jurnal Penelitian Agronomi, 2020)
Organic fertilizer expected increase number of growth and yield of pak choy. This research aims to study the influence of solid organic fertilizer and liquid organic fertilizer on growth, physiological characters, and yield of pak choy. The method used was Randomized Complete Design and three replications. The parameters observed were number of leaves, leaf area, chlorophyll content, Nitrate Reductase (NR), yield and harvest index. The result showed that the highest leaf number with 13.3 leaves was achieved by combination of SOF 20 t.ha-1 and LOF 3 times a week.  The largest leaf area was 208.44 cm2due to the application of Solid Organic Fertilizer 20 t.ha-1.The largest chlorophyll content was 0.84 mg.g-1 due to the combination treatment of SOF 20 t.ha-1 and LOF 3 times a week.  The largest NR of Pak choy is 3.51 µ mol NO2.hr-1 due to the combination treatment of SOF 20 t.ha -1 and LOF 3 times a week. The highest yields of pak choy is 29.79 kg.plot-1 is due to combination treatment SOF of 20 t.ha -1 and LOF 3 times a week, the highest harvest index was 94.6% due to combination treatment of SOF 20 t.ha -1 and LOF 3 times a week.